Cascaded Systems of Phase-Locked Loops Chaotic Syncronization - A. V. Khodunin; L. N. Kazakov (Моделирование и анализ информационных систем)
The chaotic phase synchronization of two cascaded one-ring and two-ring PLL systems in the conditions of additive and phase noise is investigated. A registration technique of the chaotic phase synchronisation on the basis of the continuous wavelet transform is developed. Onset conditions of the steady chaotic phase synchronisation are revealed. Advantages of the two-ring system of PLL over the one-ring system is shown.